2020
DOI: 10.1210/endocr/bqaa145
|View full text |Cite
|
Sign up to set email alerts
|

A New Therapeutic Approach Using a Calcilytic (AXT914) for Postsurgical Hypoparathyroidism in Female Rats

Abstract: Postsurgical hypoparathyroidism is the most common complication of thyroid surgery. Conventional therapy with high-dose calcium and vitamin D can correct hypocalcemia but can increase the risk of hypercalciuria, renal stones, or ectopic calcification. The aim of the present study was to investigate the efficacy of a calcium-sensing receptor antagonist, also called a calcilytic (AXT914), in rat models of postsurgical hypoparathyroidism. Two postsurgical hypoparathyroidism rat models were made by hemi-parathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a phase 2 clinical trial involving adults with ADH1, encaleret corrected hypocalcemia, reduced hypercalciuria, and increased PTH secretion [ 6 ]. We previously reported that AXT914, another calcilytic, increased PTH secretion and corrected abnormal calcium and phosphorus homeostasis in rats with post-surgical hypoparathyroidism [ 7 ]. Furthermore, the biochemical improvements induced by AXT914 treatment persisted even after the drug was discontinued, which implies that AXT914 might have facilitated the recovery of parathyroid tissue autotransplanted into the sternocleidomastoid (SCM) muscle, although the precise mechanism remains unclear [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase 2 clinical trial involving adults with ADH1, encaleret corrected hypocalcemia, reduced hypercalciuria, and increased PTH secretion [ 6 ]. We previously reported that AXT914, another calcilytic, increased PTH secretion and corrected abnormal calcium and phosphorus homeostasis in rats with post-surgical hypoparathyroidism [ 7 ]. Furthermore, the biochemical improvements induced by AXT914 treatment persisted even after the drug was discontinued, which implies that AXT914 might have facilitated the recovery of parathyroid tissue autotransplanted into the sternocleidomastoid (SCM) muscle, although the precise mechanism remains unclear [ 7 ].…”
mentioning
confidence: 99%
“…2019-07188). A total of 33 nine-week-old female Wistar rats were used to create a model of post-surgical hypoparathyroidism resulting from total parathyroidectomy and autotransplantation, as previously described [ 7 ]. Both parathyroid glands of each rat were removed, minced into small pieces, and put into a small pocket made in the SCM muscle.…”
mentioning
confidence: 99%